Development Of The “Awi” Bamboo Bracelet Educational Media To Improve Early Childhood Cognitive Development - Nia Kurniasih; Erna Budiarti; Chandra Apriyansyah (Kirana Publisher (KNPub), 2026)
Cognitive development in early childhood is a crucial foundation for later academic achievement. However, many early childhood education institutions still face challenges in providing effective cognitive stimulation due to limited learning media and the dominance of conventional teaching approaches. This study aimed to develop an educational medium called the “AWI” Bamboo Bracelet as a manipulative learning tool based on local cultural resources to enhance the cognitive development of children aged 5–6 years. The research employed a Research and Development (R&D) approach using the 4D development model, which includes the stages of Define, Design, and Develop. The participants consisted of 20 children in Group B at TK Islam Nurul Huda, Cibalong District, Tasikmalaya Regency. Data were collected through structured observations, interviews, expert validation sheets, teacher response questionnaires, and cognitive development assessment sheets using a one-group pretest–posttest design. Data analysis involved validity percentage calculations, normalized N-Gain analysis, and the Wilcoxon Signed Ranks Test. The results indicated that the AWI Bamboo Bracelet media was highly valid according to material experts (87%) and media experts (85%). Teacher responses showed a practicality score of 93%, categorized as very practical. The effectiveness test demonstrated a significant improvement in children's cognitive development with an overall N-Gain score of 0.69, indicating a moderate-to-high improvement. Therefore, the AWI Bamboo Bracelet media can serve as an innovative, practical, and culturally relevant learning medium to support cognitive development in early childhood education.